Learning-Based Spectrum Sensing and Access for Cognitive Radio Systems - Shehabeldin, Menatalla Diaaeldin (2015)
A Master of Science thesis in Electrical Engineering by Menatalla Diaaeldin Shehabeldin entitled, "Learning-Based Spectrum Sensing and Access for Cognitive Radio Systems," submitted in June 2015. Thesis advisors are Dr. Mohamed El-Tarhuni and Dr. Khaled Assaleh. Soft and hard copy available.